EVALUASI PRODUKSI BENIH PADA KEBUN BENIH HIBRID ACACIA (Acacia mangium x Acacia auriculiformis) DI WONOGIRI, JAWA TENGAH - Sri Sunarti; Valerianus Devi Adyantara; Suharyanto Suharyanto; Teguh Setyaji; Arif Nirsatmanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2016)
Research for developing Acacia hybrid (Acacia mangium x Acacia auriculiformis) breeding strategy through establishing hybrid seed orchard (HSO) has been started by BBPPBPTH. Two hectares of HSO was established in Wonogiri, Central Java to produce the Acacia hybrid seed. The orchard was laid out using an alternating rows design among the two pure parent species with spacing of 1 m x 3 m: 1 m within the species and 3 m between the species. The purpose of this study is to evaluate flowering synchronization and seed production in first year flowering session of four years age mother trees in the HSO. The unit area of observation was set up in 0.2 ha within the HSO. During the first flowering session, 100 mother trees (31%) were observed showing synchronized flowering time among the two parents species: 50 mother trees for Acacia mangium and 50 mother trees for A. auriculiformis. Seed production was still low in which only 38 out of 50 trees of A. mangium mother trees produced seed, whereas selected A. auriculiformis mother trees did not produce seed. The average viability of the collected seed was moderately low at 59.2%. Subsequent verification through DNA marker using SCAR and SSR revealed less than 1% of the collected seed were identified as true Acacia hybrid.